1982
DOI: 10.1002/dev.420150506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body build and arousal on newborn infant stepping

Abstract: Newborn stepping is widely believed to be a "primitive reflex" whose disappearance signals cortical maturation. Observations of normal newborns showed that the number of steps was directly related to generalized behavioral arousal. In less highly distressed infants, those who were relatively heavier for their length stepped less. These results challenge the view that stepping is reflexively released by the upright posture and support the hypothesis that the movements disappear because infants' muscle strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 19 publications
(13 reference statements)
2
40
1
1
Order By: Relevance
“…From the perspective of nonlinear dynamics, however, it has become clear that neural and behavioral changes do not map in a one-to-one way: Rates of change at the neural level might well be more gradual than those at the behavioral level (Farmer, 1990). Furthermore, the observed changes in spontaneous kicking might be influenced by changes in musculo -skeletal parameters such as absolute mass and centers of gravity of limbs and body segments (Thelen, Fisher, Ridley-Johnson, & Griffin, 1982; see also Thelen & Smith, 1994).…”
mentioning
confidence: 93%
“…From the perspective of nonlinear dynamics, however, it has become clear that neural and behavioral changes do not map in a one-to-one way: Rates of change at the neural level might well be more gradual than those at the behavioral level (Farmer, 1990). Furthermore, the observed changes in spontaneous kicking might be influenced by changes in musculo -skeletal parameters such as absolute mass and centers of gravity of limbs and body segments (Thelen, Fisher, Ridley-Johnson, & Griffin, 1982; see also Thelen & Smith, 1994).…”
mentioning
confidence: 93%
“…While two studies reported a right-foot preference for stepping (Melekian, 1981;Peters & Petrie, 1979), two others found no lateral bias in this response (Kamptner, Cornwell, Fitzgerald, & Harris, 1985;Thelen, Fisher, Ridley-Johnson, & Griffin, 1982)-a finding that also was obtained for placing (Korczyn, Sage, & Karplus, 1978). Furthermore, three other studies tested both stepping and placing in the same newborns, and again, there was a lack of consistent findings.…”
mentioning
confidence: 79%
“…As for expressions of ''footedness,'' two other considerations stem from the work of Thelen et al (1982). One concerns individual differences in body build or, in our case, the relative masses of the newborn's legs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, early work by Thelen and colleagues [Thelen, Fisher, & RidleyJohnson, 1984;Thelen, Fisher, Ridley-Johnson, & Griffin, 1982] focused on infant locomotion. They showed that the infant stepping reflex (order parameter) is a function of the infant's leg strength (control parameter).…”
Section: Catastrophe Modelsmentioning
confidence: 99%